Resilience of FDI Inflows Against Global Economic Shocks: Evidence from BRICS and ASEAN 5 Countries - Darussalam; Nguyen Thi Hong Thuy; Naila Erum; Afroza Yasmin Mitu (CV. Era Digital Nusantara, 2026)
Foreign Direct Investment (FDI) drives emerging markets but faces increasing global volatility due to macroeconomic instability. This study analyzes and compares FDI resilience between BRICS and ASEAN 5 during the Eurozone Crisis (2012–2013) and the COVID-19 pandemic (2019–2020). Using secondary data from the World Bank (2010–2023), this quantitative study explicitly employed an independent sample t-test and Mann-Whitney U test to measure the statistical significance of FDI resilience differences between the two blocs across crisis and post-crisis periods. The results reveal significant divergence: BRICS experienced sharp FDI declines during the pandemic due to structural vulnerabilities like commodity dependence and political instability. Conversely, ASEAN 5 demonstrated stronger adaptability, rebounding rapidly to an average of 2.94% of GDP in the post-crisis period, with Vietnam leading at 4.3% and Indonesia stabilizing at 1.7%. Statistically, while the t-test showed descriptively higher resilience for ASEAN 5 during the initial shock, the Mann-Whitney U test confirmed that ASEAN 5’s FDI recovery was significantly stronger than that of BRICS in the post-crisis period (p < 0.05). Theoretically, this enriches the discussion on FDI resilience against multidimensional crises, proving that dynamic policy resilience can override static market-size advantages. Practically, BRICS requires deeper structural reforms, while ASEAN 5 must sustain fiscal responsiveness and regional integration to maintain momentum. Ultimately, this research provides a practical blueprint for policymakers to design shock-responsive economic frameworks and offers global investors strategic insights for capital allocation and risk mitigation in emerging markets.